Historiographical approaches and social representations in textbooks. A comparative study, Spain-France-England - Gómez Carrasco, Cosme J.; Chapman, Arthur (Historia y Memoria de la Educación, 2017)
This paper analyzes the historiographical approaches and national, European and extra-European social representations in Secondary Education textbooks in Spain, France and England. We have chosen for the sample 18 textbooks used in the first two years of secondary education in the three countries, and. we have selected three large, renowned publishers within each country (Anaya, Oxford and Vicens Vives for Spain; Belin, Bordas and Lelivrescolaire for France, and Collins, Heinemann and Hodder Education for England). The results show different historiographical approaches in the textbooks analyzed, with a greater pre-eminence of structuralism and positivism in the Spanish case; a clear influence of the latest generations of Annales in the French case; and a greater importance given to social history and history-from-below in the English case. The three countries also differ in social representations; French and Spanish textbooks treat historical accounts within a European framework to which they feel they belong, while the English textbooks present the construction of the English nation (especially in the Middle Ages and the Modern Age) from a very Anglo-centric perspective.